FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PASANGAN USIA SUBUR TERHADAP PEMAKAIAN METODE KONTRASEPSI JANGKA PANJANG (MKJP) IMPLAN - Candra Dewinataningtyas (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
The population of Indonesia in 2020 is 267,026,366 people, which makes Indonesia the fourth most populous country. Then according to reports until mid-2022 that number has increased to 275.77 million people, the rate of population growth has increased 1.13% from last year. For this reason, promoting family planning (KB) is an effort to build quality families. Implanted contraception is a Long Term Contraceptive Method (MKJP) which is recommended for preventing unwanted pregnancies because it has a high level of effectiveness in terms of usability and cost, achieving a 99% success rate. The purpose of this study was to identify the factors of age, level of education, and level of knowledge on the interest of couples of childbearing age in using implanted contraceptives and to analyze the dominant factors that influence them. The research was conducted in Banaran Village, Kediri City in April 2023. This type of research is analytic with a cross sectional approach. The sampling technique used was quota sampling, the number of respondents was 210 PUS who met the inclusion and exclusion criteria. The research instrument used checklists and questionnaires with the Spearman test data analysis technique followed by multiple logistic regression tests. The results showed that there was a relationship between age and interest with a p value of 0.033, there was a relationship between educational level and interest with a p value of 0.000 and there was a relationship between knowledge and interest with a p value of 0.000. The factor with the largest Exp (β) is the knowledge level factor with Exp (β) values of 18.178 and 127.495. The conclusion obtained is that there is a relationship between age, education level, and level of knowledge on the interest of couples of childbearing age in the use of implanted contraceptives. The dominant factor influencing the interest of couples of childbearing age in using implanted contraceptives is the level of knowledge.